SYSTEMATIC REVIEWS: BALIA LOCAL WISDOM AS A HEALTHY SOLUTION TO KAILI - arwan, arwan; pitriani, pitriani (Tadulako University, 2017)
Background and Objetive: A community which still performs a traditional ceremony called “Balia” can befound in Balaora Village, In South Sulawesi, Indonesia. Although modern health services already exist, theBalia is a tradition of To Kaili community in solving their health problem. Material and Method: Themethod used is a systematic review of literature, a procedure performed by collect of information fromseveral related sources to study the topic, then cataloging and documentation. Results: As an example ofsocial behavior, when they suffer a disease, they prefer to visit a shaman rather than a medical doctor oreducated health professionals. Another fact is when the folks fail in curing their health problems by modernhealth services, they will back to the traditional method such as a shaman or traditional herbs. Baliaceremony had existed long time ago and it is believed to be beneficial to To Kaili. According to their belief,the Balia ceremony is able to cast out evils in the human body. In a performance of the Balia Dance, all thedancers and participants need to involve their soul and felling; the attention must be concentrated into theceremony.. Conclusion: The tradition of Balia as ancestral belief is believed to avoid all kinds of calamitiesand healing media. Therefore, the community thinks that there is no harm to perform it. Therefore, thetradition of Balia must be preserved and kept as an alternative for health problem of To Kaili in this modernera.